The Impact of Human Resources Information Systems on the Individual Performance of Workers in Algerian Economic Enterprises - Djebiret, Sana (Jordan Journal of Business Administration, 2021)
This study aimed at identifying the impact of human resources information systems on individual performance through the elaboration of a multi-dimensional and applicable conceptual model consisting of nine measures that fall under three basic variables: the precedences of the value in use of human resources information systems, the value in use of human resources information systems and individual performance. For this purpose, a questionnaire with 80 items was developed and distributed to a sample of 140 users of human resources information systems in seven economic enterprises in the region of Biskra. After analyzing the data using the structural equation and the regression analysis, a number of results were obtained. The most important results were: First, the existence of a statistically significant effect of the precedences of the value in use of human resources information systems on individual performance. Second, the existence of a statistically significant effect of the value in use of human resources information systems on individual performance. Third, the existence of a statistically significant effect of the precedences of human resources information systems on individual performance through the value in use of human resources information systems. This last variable had the most significant effect as a partial mediator on most of the model relationships. The study recommended the decision makers in the enterprises investigated to enhance the value in use of human resources information systems and monitor its development at the external level as an important factor in achieving the desired benefits of these systems, as well as the precedences of the value in use of systems as elements that ensure the desired results from the use of such systems.